2022
DOI: 10.31083/j.ceog4904079
|View full text |Cite
|
Sign up to set email alerts
|

Foetal pain and anaesthesia during prenatal surgery

Abstract: Objectives: Foetal surgery is a relatively new branch of medicine; the health providers involved are currently wondering what kind of anaesthesia should be provided to the foetuses. In the last few years, new advances have been reported on foetal sensoriality and capability for feeling pain; meanwhile alerts have been issued on the risks of prolonged anaesthesia in the early infancy. Aim of this paper is reviewing the main data on foetal pain, to be aware of which is the time in pregnancy when it is likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…Implications of fetal pain perception at earlier gestational ages include the need for research in fetal pain assessment and management strategies to ensure adequate procedural and post-procedural pain control ( 3 , 57 , 58 ) and to prevent adverse short- and long-term sequelae, including the potential for preterm labor ( 1 , 18 ). An ethical obligation also exists to prevent, mitigate, and treat pain whenever it can be anticipated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Implications of fetal pain perception at earlier gestational ages include the need for research in fetal pain assessment and management strategies to ensure adequate procedural and post-procedural pain control ( 3 , 57 , 58 ) and to prevent adverse short- and long-term sequelae, including the potential for preterm labor ( 1 , 18 ). An ethical obligation also exists to prevent, mitigate, and treat pain whenever it can be anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that fetuses demonstrate discriminative facial expressions of acute pain following intramuscular injection ( Figures 7 , 8 ) ( 16 , 58 ). Researchers emphasized the need for continuous monitoring of fetal activity and responses to invasive fetal procedures to better assess and treat procedural and post-procedural pain ( 3 ).…”
Section: Fetal Responses To Noxious Stimulimentioning
confidence: 99%
See 1 more Smart Citation